HIV-1 Gag-protease-driven replicative capacity influences T-cell metabolism, cytokine induction, and viral cell-to-cell spread - Omolara O. Baiyegunhi; Kensane Mthembu; Ann-Kathrin Reuschl; Doty Ojwach; Omotayo Farinre; Murunwa Maimela; Sheila Balinda; Matt Price; Madeleine J. Bunders; Marcus Altfeld; Clare Jolly; Jaclyn Mann; et al. (mBio)
ABSTRACT High replicative capacity (RC) HIV-1 strains are associated with elevated viral loads and faster disease progression in the absence of antiretroviral therapy. Understanding the mechanisms by which high RC strains adversely affect the host is essential for developing novel anti-HIV interventions. This study investigates cellular metabolism, cytokine induction, and cell-to-cell spread as potential mechanisms differentiating clinical outcomes between low and high RC strains of HIV-1. We constructed chimeric viruses containing patient-derived gag-proteases from HIV-1 subtypes B and C in the NL4-3 backbone. Viral RC was determined using a green fluorescent protein (GFP)-reporter T-cell line assay and cytokine production in T-cells was assessed using Luminex. Virus cell-to-cell spread efficiency was measured through flow cytometry-based detection of p24, while nutrient uptake assays and mitotracker dye detection served as surrogate markers for T-cell metabolism and mitochondrial function. Chimeric subtype C viruses exhibited significantly lower RC compared to subtype B viruses (P = 0.0008). Cytokine profiling revealed distinct cytokine signatures associated with low RC subtype C viruses. Viral RC negatively correlated with tumor necrosis factor alpha (TNF-α), IL-8, and IL-13 induction, while it positively correlated with platelet-derived growth factor (PDGF-bb), IL-7, monocyte chemoattractant protein-1 (MCP-1), fibroblast growth factor (FGF)-basic levels, viral spread efficiency (P = 0.008, r = 0.5), and cellular glucose uptake (P = 0.02, r = 0.5). Conversely, RC was negatively correlated with glutamine levels (P = 0.001, r = −0.7), indicating a link between RC and nutrient utilization. Furthermore, mitochondrial depolarization was elevated in subtype B infections when compared to subtype C infections (P = 0.0008). These findings indicate that high RC strains exert distinct cellular effects that may influence HIV-1 pathogenesis, highlighting the need to develop novel therapeutic strategies.IMPORTANCEVirus replicative capacity (RC) influences disease progression following HIV-1 transmission; however, the mechanisms underlying the differential clinical outcomes remain poorly understood. Our study reveals variations in cytokine induction and cellular metabolism in T-cells infected with HIV-1 subtype B and C viruses exhibiting high or low RC. T-cells infected with high RC strains showed increased induction of IL-7 and platelet-derived growth factor (PDGF-bb), along with heightened glucose uptake and elevated glutamine consumption compared to those infected with low RC strains. By contrast, low RC strains induced higher levels of IL-8, IL-13, and tumor necrosis factor alpha (TNF-α) and demonstrated reduced efficiency in modulating cellular metabolism and virus cell-to-cell spreadability. These findings highlight distinct biological differences between high and low RC viruses, providing valuable insights into the mechanisms that may underpin varying clinical outcomes. This knowledge may inform the development of novel interventions aimed at limiting viral virulence or transmission.